Perinatal Outcome in Cases of Isolated Oligohydroamnios at Term at Tertiary Care Center of Wah Cantt & HIT Taxilla - Khair-un-Nisa, Rukhsana Shaheen Afzal, Aqsa Munawer Qureshi, Irum Mushtaq, Ayesha Akram, Adeela Amin (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Measurement or quantitative estimation of liquor/ amniotic fluid is an integral part of routine obstetrical scan. Amniotic fluid index (AFI) is calculated as the sum of deepest pocket of fluid in the four quadrants of the gravid uterus. Amniotic fluid is essential for fetal growth and development. It provides a protective cushion against any external force/trauma and allows the movement of fetus and its growth. It is an essential part of BPP (Biophysical profile) and its values correlate well with adequacy of renal perfusion. Abnormalities of AFI can interfere with the fetal development and may serve as an indicator for underlying fetal or maternal disease. Objective: To determine the frequency of perinatal outcomes in cases of isolated oligohydroamnios those were induced at term. Study Design: Cross sectional study Place and Duration of Study: Department of Obstetrics & Gynaecology, Pakistan Ordinance Factories Hospital, Wah Cantt, Aero Hospital, AWC. Wah Cantt and HITEC-IMS, HIT Hospital, Taxilla Cantt from 1st January 2017 to 31st December 2018. Methodology: Eighty two patients presenting with oligohydroamnios, age of female 22-38 years, AFI 5cm or less, single alive intrauterine fetus with cephalic presentation having 37 completed weeks of gestation and intact membrane were included. Results: The mean age was 28±3.07 years of females. The mean birth weight of infants was 3.2±0.6 Kg, mean gestational age of newborn was 36±1.2 weeks. 41(50%) were delivered through spontaneous vaginal delivery and other 41 (50%) were delivered through caesarean delivery. Mean APGAR score at 1 min was 6.48 and at 5 min mean APGAR Score was 8.3 and 31 (38%) were admitted in NICU. Conclusion: Pregnant women with oligohydroamnios can be identified by a good clinical examination and further can easily be confirmed by a non-invasive ultrasonography by measuring AFI.